Long-term donor site morbidity in head and neck cancer patients and its impact on quality of life: a cross-sectional study. Issue 7 (July 2019) - Kansy, K.; Hoffmann, J.; Alhalabi, O.; Mistele, N.; Freier, K.; Shavlokhova, V.; Mertens, C.; Freudlsperger, C.; Engel, M.
Abstract: Modern head and neck reconstructive surgery offers a multitude of different reconstructive options. In such cases, donor site morbidity is an important factor in the affected patient's decision-making. The aim of this study was to perform an objective comparison of donor site morbidity for the five most frequent microvascular donor sites in head and neck reconstructive surgery (radial forearm, anterolateral thigh, fibula, iliac crest, and scapula) using a uniform testing system. In this cross-sectional study, 117 donor sites were analyzed (106 for malignant disease and 11 for non-malignant disease): 73 radial forearm, 14 scapula, 12 anterolateral thigh, 10 fibula, and eight iliac crest. Testing consisted of range of motion, muscle strength, and sensation. The non-affected side served as the control. Quality of life was assessed using the Washington Quality of Life Questionnaire version 4 in its German translation. Range of motion was restricted in 15 cases (12.8%). Muscle strength was decreased in 58 cases (49.6%). Sensation was reduced in 70 cases (60%). Concerning quality of life, 31.2% of patients were limited in their daily activities. The scapula flap showed the highest incidence of overall donor site morbidity. However, correlation between objective and subjective donor site impairment was weak and the majority of patients experienced only minor limitations.